2012
DOI: 10.1007/s00018-012-1003-8
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribose) polymerase-2: emerging transcriptional roles of a DNA-repair protein

Abstract: Abstract:Poly(ADP-ribose) polymerase (PARP)-2 is a nuclear enzyme that belongs to the PARP family and PARP-2 is responsible for 5-15% of total cellular PARP activity. PARP-2 was originally described in connection to DNA repair and in physiological and pathophysiological processes associated with genome maintenance (e.g. centromere and telomere protection, spermiogenesis, thymopoesis, azoospermia and tumorigenesis). Recent reports identified important rearrangements in gene expression upon the knockout of PARP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 114 publications
(176 reference statements)
1
41
0
1
Order By: Relevance
“…Furthermore, it will be important to determine the involvement of further members of the PARP family in the regulation of inflammatory processes. Some of them have already been shown to associate with inflammatory pathologies: such as PARP-2 (reviewed in [35]), PARP-3 [36], tankyrases [79], or PARP-14 [30,31]. Moreover, poly(ADP-ribose) glycohydrolase has been implicated in the regulation of immune functions [80,81] underlining the central role of poly(ADP-ribosyl)ation in inflammation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it will be important to determine the involvement of further members of the PARP family in the regulation of inflammatory processes. Some of them have already been shown to associate with inflammatory pathologies: such as PARP-2 (reviewed in [35]), PARP-3 [36], tankyrases [79], or PARP-14 [30,31]. Moreover, poly(ADP-ribose) glycohydrolase has been implicated in the regulation of immune functions [80,81] underlining the central role of poly(ADP-ribosyl)ation in inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…PARPs other than PARP1 may also alter the production of chemokines and cytokines. Deletion of PARP-2 leads to alterations in the transcriptome, notably in the expression of genes involved in inflammatory regulation [reviewed in [35]]. Interestingly there seems to be an overlap with the inflammatory genes dysregulated upon PARP-1 ablation: e.g.…”
Section: Cytokines and Chemokinesmentioning
confidence: 99%
“…PARP2, like PARP1, catalyzes the poly(ADP-ribosyl)ation of several nuclear proteins with nicotinamide adenine dinucleotide (NAD + ) as a substrate. 32,33 Although the majority of Role of PARP1 in E2F1-induced apoptosis A Kumari et al cellular poly(ADP-ribosyl)ation is attributed to PARP1, PARP2 may act as an alternative enzyme, particularly when PARP1 is unavailable. 32,33 Similar to other small-molecule PARP inhibitors, olaparib inhibits not only PARP1 but also PARP2.…”
Section: Resultsmentioning
confidence: 99%
“…In the HeLa cell model used in our laboratory, the lower PARG protein levels seen in the PARP-2 stably depleted cells was a consequence of decreased PARG mRNA level (our unpublished data) suggesting a direct role of PARP-2 in the regulation of the expression of PARG. Indeed, recent reports have revealed that the depletion of PARP-2 modifies the activity of multiple transcription factors and in particular it is involved in the transcriptional regulation of metabolism and oxidative stress responses [55].…”
Section: Factors Affecting Cancer Cell Radiosensitivitymentioning
confidence: 99%